Resolusi Konflik di Dunia Islam: Studi Kasus Al-Shabaab di Somalia - Giyandra Meisarani (Universitas Airlangga, 2019)
This paper discusses conflict resolution on problems in Somalia byprinciples taught in the Islamic world. The conflict in Somalia regardingjihadist group al-Shabaab has become an international issue. Somaliaitself is a country that has just a strong government system, and hasjust recognized by international community. This phenomenon then ledto many attacks conducted by the Al-Shabaab. The attacks made Somalipeople who were not members of al-Shabaab felt insecure. With theassistance that came to the Somali government, al-Shabaab felt defensivetowards foreign countries, as well as international organizations such asIntergovernmental Authority on Drought and Desertification (IGADD)and the African Union. This is due to the fact that they felt that the assistanceprovided would affect Somalia, as they wanted to make the country with awhole Islamic system without the interference of western countries. In thegiven conflict resolution above, it adjusts to what has been taught by theProphet Muhammad who put forward peace and prosperity as an Islamicstate.